Isolation and Characterization of a New Phage Infecting Elizabethkingia anophelis and Evaluation of Its Therapeutic Efficacy in vitro and in vivo - Peng, Shih-Yi; Chen, Li-Kuang; Wu, Wen-Jui; Paramita, Prajna; Yang, Po-Wei; Li, Yun-Zhong; Lai, Meng-Jiun; Chang, Kai-Chih (Frontiers in Microbiology, 2020)
Elizabethkingia spp. are a group of non-fermentative, Gram-negative, catalase-positive and non-motile bacilli. They can cause meningitis in neonates and immunosuppressed patients, and lead to high mortality. Considering the rising trend of drug resistance among bacteria pathogens, bacteriophage (phage) therapy is a potential alternative to antibiotics for treating multidrug-resistant bacterial infections. However, so far no phages specific for Elizabethkingia spp. have been reported. Using a clinically isolated Elizabethkingia anophelis as the host, the phage TCUEAP1 was isolated from wastewater of Hualien Tzu Chi hospital. The phage particle of TCUEAP1 under electron microscopy was revealed to belong to the siphoviridae family, with a head size of 47 nm, and a tail dimension 12 nm in diameter and 172 nm in length. The one-step growth analysis showed that the latent period of TCUEAP1 was about 40 minutes with a rise period lasting about 20 minutes, yielding a burst size of approximately 10 PFU/cell. The adsorption rate of TCUEAP1 reached about 70% in 20 minutes. Using 20 isolates of Elizabethkingia spp to test the host range of TCUEAP1, it displayed narrow spectrum infecting three strains of E. anophelis, but forming spot lysis on 16 strains. The sequence result showed that the genome of TCUEAP1 is a double-stranded DNA of 49,816 bp, containing 73 predicted open reading frames. Further genomic analysis showed TCUEAP1 to be a new phage with no resemblance to publicly available phage genomes. Finally, in a mouse intraperitoneal infection model, at 6 h after the bacterial injection, TCUEAP1 decreased the bacterial load by 5-fold in blood. Also, TCUEAP1 rescued 80 percent of mice heavily infected with E. anophelis from lethal bacteremia. We hope the isolation and characterization of TCUEAP1, the first phage infecting Elizabethkingia spp, can promote more studies of the phages targeting this newly emerging bacterial pathogen.